2007
DOI: 10.1090/s0002-9939-07-09003-x
|View full text |Cite
|
Sign up to set email alerts
|

Separating classes of composition operators via subnormal condition

Abstract: Abstract. Several classes have been considered to study the weak subnormalities of Hilbert space operators. One of them is n-hypnormality, which comes from the Bram-Halmos criterion for subnormal operators. In this note we consider E(n)-hyponormality, which is the parallel version corresponding to the Embry characterization for subnormal operators. We characterize E(n)-hyponormality of composition operators via k-th Radon-Nikodym derivatives and present some examples to distinguish the classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…. , f n ∈ H. Based on Embry's characterization, McCullough and Paulsen introduced in [24] a new class of operators which, following [17], will be called E(n)-hyponormal: T is said to be E(n)-hyponormal (n ≥ 1) if inequality (1.2) holds for all f 0 , . .…”
Section: Towards L(n)-hyponormalitymentioning
confidence: 99%
See 1 more Smart Citation
“…. , f n ∈ H. Based on Embry's characterization, McCullough and Paulsen introduced in [24] a new class of operators which, following [17], will be called E(n)-hyponormal: T is said to be E(n)-hyponormal (n ≥ 1) if inequality (1.2) holds for all f 0 , . .…”
Section: Towards L(n)-hyponormalitymentioning
confidence: 99%
“…As shown in [24], E(1)-hyponormality is essentially weaker than 1-hyponormality. Moreover, in view of [17], T is E(1)-hyponormal if and only if |T | 4 ≤ |T 2 | 2 , and so, by the Heinz inequality, such T must be an A-class operator, that is, |T | 2 ≤ |T 2 | (see [14, p. 166]). Hence, E(n)-hyponormality can be thought of as a bridge between subnormal operators and A-class operators.…”
Section: Towards L(n)-hyponormalitymentioning
confidence: 99%
“…Motivated by these previous results and the criterion for subnormality of general unbounded operators due to Stochel and Szafraniec (see [27,Theorem 3]), we introduce in this paper classes S * n,r of unbounded operators closely related to cosubnormal operators (they resemble, in a sense, weak hyponormality classes studied in the case of bounded operators, cf. [22,20,15,19]) and investigate under what conditions composition operators with infinite matrix symbols belong to the classes. We use inductive limits to achieve our goal.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the p-hyponormality notion is contained in such studies. Jung-Lee-Park( [7]) constructed examples induced by some block matrix operators, and in [6], the classes of p-hyponormal operators are distinct with respect to positive real numbers p. In [1] and [2] Burnap-Jung-Lambert discussed some composition operator models on L 2 , and also they showed that the classes of p-hyponormal and p-paranormal operators are distinct for each p > 0. Nonetheless, new examples for the p-hyponormal operator classes are needed to study the relationship between the above two notions.…”
Section: Introductionmentioning
confidence: 99%